2021
DOI: 10.3389/fpls.2021.782072
|View full text |Cite
|
Sign up to set email alerts
|

Phenotyping of Different Italian Durum Wheat Varieties in Early Growth Stage With the Addition of Pure or Digestate-Activated Biochars

Abstract: This study aims to highlight the major effects of biochar incorporation into potting soil substrate on plant growth and performance in early growth stages of five elite Italian varieties of durum wheat (Triticum durum). The biochars used were obtained from two contrasting feedstocks, namely wood chips and wheat straw, by gasification under high temperature conditions, and were applied in a greenhouse experiment either as pure or as nutrient-activated biochar obtained by incubation with digestate. The results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The commercial requirements for an alternative to seed coating as a competitive delivery system demand a tool that also meets the high safety standards [ 49 ]. Studies including greenhouse and field trials have been focused on this topic for the last 20 years [ 50 ]. Quantitative data previously reported for wheat showed that char functionalization was more efficient than seed coating in boosting the biomass of both roots and shoots.…”
Section: Resultsmentioning
confidence: 99%
“…The commercial requirements for an alternative to seed coating as a competitive delivery system demand a tool that also meets the high safety standards [ 49 ]. Studies including greenhouse and field trials have been focused on this topic for the last 20 years [ 50 ]. Quantitative data previously reported for wheat showed that char functionalization was more efficient than seed coating in boosting the biomass of both roots and shoots.…”
Section: Resultsmentioning
confidence: 99%
“…The wheat seedlings were watered regularly as needed from the bottom, and no further fertilizer was used during the experiment. The wheat plant developmental stage was described using the BBCH-scale [29,30]. During the one-leaf stage (BBCH 7), only one seedling, each of a similar plant size, was kept in each pot, and the other extra seedlings were individually removed from each pot.…”
Section: Plant Growth Conditionsmentioning
confidence: 99%